2005
DOI: 10.17221/3630-pse
|View full text |Cite
|
Sign up to set email alerts
|

Water logging may inhibit plant growth primarily by nutrient deficiency rather than nutrient toxicity

Abstract: The aim of our experiments was to investigate whether nutrient deficiency or toxicity is the cause for growth inhibition of wheat and barley in waterlogged soils. Experiments using two soils (top and subsoil) differing largely in various characteristics revealed a growth inhibition of wheat and barley in the case of subsoil due to water logging, without Fe or Mn toxicity. Water culture experiments with anaerobic (N 2 ) and aerobic aeration confirmed that oxygen deficiency did not induce nutrient toxicity (Fe, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 20 publications
4
70
0
4
Order By: Relevance
“…At the end of experiment, the effects of the interaction between water and fertilization on plant height, leaf area, and dry mass accumulation (including total biomass, root, stem and leaf mass) were significant. Water and nutrient stresses suppressed growth rate, as also previously observed (Hsiao, 1973;Munns, 2002;Karageorgou et al, 2002;Stefens et al, 2005;Song et al, 2010;Weih, 2010). Judging by the variance of plant growth in Table 1, there was no significant difference between water and nutrient stress, when applied separately on plant growth.…”
Section: Discussionsupporting
confidence: 83%
“…At the end of experiment, the effects of the interaction between water and fertilization on plant height, leaf area, and dry mass accumulation (including total biomass, root, stem and leaf mass) were significant. Water and nutrient stresses suppressed growth rate, as also previously observed (Hsiao, 1973;Munns, 2002;Karageorgou et al, 2002;Stefens et al, 2005;Song et al, 2010;Weih, 2010). Judging by the variance of plant growth in Table 1, there was no significant difference between water and nutrient stress, when applied separately on plant growth.…”
Section: Discussionsupporting
confidence: 83%
“…Singh et al (2002) also reported that the detrimental effects of water stagnation on sunflower were greater at the six-to eight-leaf stage (50 days after sowing) than at the fl owering stage (80 days after sowing). Steffens et al (2005) reported that the oxygen defi ciency in waterlogged soil inhibited ATP synthesis, leading to decreased nutrient uptake. In the present study, we examined the response of root growth to waterlogging.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of oxygen availability for root respiration and the production of soil phytotoxins, which inhibit root formation and promote root decay, causes a reduction in overall root growth. Root conductance for water and nutrient uptake is decreased by waterlogging resulting in nutrient deficiency in plants [10,11]. Plant leaves can turn yellow due to a significant decrease in plant N content resulting from reduced root activity under waterlogged conditions [12].…”
Section: Introductionmentioning
confidence: 99%